Robotic evaluation of a 3D-printed scaffold for reconstruction of scapholunate interosseous ligament rupture: a biomechanical cadaveric study - Alastair R.J. Quinn; Jayishni N. Maharaj; Randy Bindra; Amelia Carr; Natividad Gomez; Kaecee Fitzgerald; Nataliya Perevoshchikova; Cedryck Vaquette; Claudio Pizzolato; Minghao Zheng; David Lloyd; David J. Saxby (PeerJ)
Background Rupture of the scapholunate (SL) interosseous ligament (SLIL) is a challenging injury to treat surgically due to the small and complex nature of the SL linkage. This study was a preliminary robotic assessment of the immediate biomechanical effects of a novel 3D-printed scaffold used to reconstruct the ruptured SLIL. Methods Nine minimally loaded cadaveric wrists underwent robotically manipulated flexion-extension and radial-ulnar deviation under conditions of intact, transected, and reconstructed SLIL. Simulated radiographic measures (i.e., SL angle and SL gap) and three-dimensional SL gap across wrist motions were used to assess static and dynamic stability of the reconstructed SLIL. Results Three cadaveric specimens produced complete results across all experimental conditions. Intact SL linkage had a SL angle comparable (but slightly lower) than normative literature values. Once the native SLIL was transected, SL angle disruption was evident, and largely restored once the scaffold was surgically installed. Similar results were seen for SL gap. Results of the dynamic three-dimensional SL gap indicated the scaffold restored dynamic stability to a limited extent. Conclusion Static and dynamic stability of the SL linkage was not compromised by surgical installation of the scaffold. Scaffold installation provided limited restoration of SL linkage towards native values; however, the small number of cadaveric specimens and minimal articular loading applied to the radiocarpal joint limits generalization. Overall, the scaffold may provide adequate mechanical fixation of the SL linkage and enable biological ingrowth of ligament.